1999
DOI: 10.1046/j.1460-2695.1999.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray diffraction studies on fatigue crack plastic zones developed under plane strain state conditions

Abstract: An overview of the X‐ray fractography technique, as performed on fatigue crack surfaces of several steels and Al‐alloys under different loading conditions, is presented. The plastic zone sizes of fatigue cracks, for plane strain conditions, are measured from the in‐depth distribution of residual stresses and X‐ray diffraction peak broadening. In addition to the usual monotonic plastic zone size determination methodology, a model for the estimation of the reverse plastic zone size was established in the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…It is interesting to compare the data obtained for R = 0.1 and Δ K = 13 MPam 1/2 and R = 0.35 and Δ K = 13 MPam 1/2 : in the second case the larger K max causes an increment of the cyclic plastic radius r pc and a deeper plastic zone. This is different from previous observations 12 where the decreasing‐increasing‐decreasing trend is related only to the value Δ K and not to R .…”
Section: Xrd Analysis Of the Crankshaftcontrasting
confidence: 99%
See 1 more Smart Citation
“…It is interesting to compare the data obtained for R = 0.1 and Δ K = 13 MPam 1/2 and R = 0.35 and Δ K = 13 MPam 1/2 : in the second case the larger K max causes an increment of the cyclic plastic radius r pc and a deeper plastic zone. This is different from previous observations 12 where the decreasing‐increasing‐decreasing trend is related only to the value Δ K and not to R .…”
Section: Xrd Analysis Of the Crankshaftcontrasting
confidence: 99%
“…Bignonnet et al ., 10 Lebrun et al ., 11 Dias et al 12 . focussed their attention on the relation between the monotonic and cyclic plastic zones extension, the value of K max and Δ K , the measure of the residual stresses and of the FWHM: original results were found, in particular a model for the estimation of the reverse plastic zone in the case of fatigue softening materials that is based on the diffraction peak broadening (FWHM) in‐depth distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Given that a diffraction peak is generally broadened by plastic deformation, the variation in the peak full width at half maximum (FWHM) across the fracture surfaces has been used previously to assess the plastic zone and thereby the stress intensity experienced at the crack tip [40]. Withers [41] has shown that synchrotron x-ray diffraction measurements within steep stress gradients can result in significant peak broadening that might be misinterpreted as a result of plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…From the X-ray measurements it is also possible to take another information related to the modification of the surface properties induced by shot peening [12]. This information comes from the width of the diffraction peak, taken at one half of the peak (FWHM), that is, an index of the grain distortion and of the dislocation density, thus being a parameter that locally identifies the hardening induced by shot peening.…”
Section: Experimental Analysis and Resultsmentioning
confidence: 99%